Organisasi Profesi: Integritas dan Tanggung Jawab - Robbani, Hamzah (Neolectura, 2025)
Public trust constitutes the primary foundation of the relationship between society and professional groups, which is institutionally mediated by professional organizations. In practice in Indonesia, professional organizations have often not optimally fulfilled their public mandate as guarantors of their members’ integrity, competence, and accountability. This condition is reflected in the growing public distrust, the increasing number of professional service disputes that culminate in the criminalization of professions, and the strong perception of corporatist protection within internal ethical mechanisms. This study aims to analyze the meaning of the role of professional organizations amid an integrity crisis, while also formulating a model for reconstructing accountability oriented toward public protection. The research employs a qualitative approach with a transcendental phenomenological design, using in-depth interviews with victims of professional services, professionals facing ethical or legal proceedings, and regulators within professional organizations. The findings indicate a disparity between the ideal function of certification as a quality assurance mechanism and the reality of weak supervision, the absence of early detection systems, and the lack of measurable service standards. Professional organizations tend to adopt reactive, administrative, and procedural approaches, thereby failing to prevent breaches of contract and malpractice in a systemic manner. This study proposes a reconstruction of the role of professional organizations through the implementation of collective responsibility based on vicarious liability, mandatory professional insurance, and the establishment of a professional compensation fund to restore national public trust.